Triangular cooperation for soil and water management for the sustainability of the agrifood systems of Caribbean countries - Casimir, Al-Mario (2023)
This report compiles the problems, challenges and opportunities when creating new strategies for sustainable governance of natural resources in the Caribbean, describing, at the same time, an experience of triangular cooperation triggered by regional challenges. Specifically, this publication contributes to the updating of strategic planning and technologies for governance on water and soil management in Caribbean countries, in the context of the post COVID-19 pandemic. The compilation of Chapters I to VII summarises the regional dialogue held through virtual and in site exchanges that have been organized to strengthen the articulation between the partners of the project between 2021 and 2023 (August). In Chapter VIII, is an overview of the actions taken and the challenges for triangular cooperation for strengthening public policies and international cooperation for sustainable development. In the conclusions, INTA´s specialist highlighted some reflections about the implementation of environmental policies for the conservation and sustainable management of natural resources; the development of renewable energies and energy efficiency and the added value that the international cooperation promotes seeking innovation and sharing knowledge to reach new global public goods.